field work: opportunity or conflict. a reflection on the learning of the methodology (Revista Electrónica REDINE, 2018)
This paper presents a reflection about entering the field work during the course of an investigation, particularly regarding the differences that might exist between doing fieldwork and collecting data, since one of the most important aspects of the discussion of this point relates to what might be called bargaining process between the researcher and the subjects with which it interacts, especially with key informants. Similarly, addresses some problems that appear during this phase, among which are certain deficiencies in the collection of data, such as those that occur when passes relevant information. Another aspect to highlight concerns the circumstances presented to use observation, associated with three benchmarks: context, researcher and subject, in terms of its possible impact on data recovery.
Keywords: development of field; data collection; informants